THE CONCEPT OF MODELING THE DEVELOPMENT OF THE TERRITORIES OF THE RUSSIAN PART OF THE BARENTS EURO-ARCTIC REGION: INSTITUTIONAL AND FUNCTIONAL APPROACH - N. Didenko; D. Skripnuk (Модернизация, инновация, развитие)
The article presents a model of development in the Russian part of the Barents Region on the basis of institutional and functional approach. At the heart of the institutional and functional approach in constructing the model of territorial development is the idea of describing the socioeconomic space of the territory in terms of the institutional environment. The institutional environment in this model is characterized by a state of social, economic, industrial and environmental spheres of human activity in the region, the development of which increases the potential for human development. The model describes the state of the institutional environment, including (1) the interaction of organizations and actors; (2) The process of interaction between organizations and the environment; (3) the eff ectiveness of the actors. The actors in the institutional and functional model of territorial development companies are economic entities that refl ect the specifi cs of the industry and the industrial and economic structure of the regional economy, as well as the population living and working in the region. Organizations in the model are such institutions, organizations that (1) regulate the actions of the various actors of socio-economic, industrial and environmental processes taking place in the socio-economic environment of territories; (2) regulate the activities of various actors directly involved themselves in these processes. Institutional and functional development model developed for the territories of the Russian part of the Barents Region.